Safety and efficacy of bulevirtide in combination with tenofovir disoproxil fumarate in patients with hepatitis B virus and hepatitis D virus coinfection (MYR202): a multicentre, randomised, parallel-group, open-label, phase 2 trial - Wedemeyer, Heiner; Schöneweis, Katrin; Bogomolov, Pavel; Blank, Antje; Voronkova, Natalia; Stepanova, Tatiana; Sagalova, Olga; Chulanov, Vladimir; Osipenko, Marina; Morozov, Viacheslav; Geyvandova, Natalia; Sleptsova, Snezhana; et al. (The lancet. Infectious diseases, 2022)
Background - Bulevirtide is a first-in-class peptidic entry inhibitor for hepatitis B virus (HBV) and hepatitis D virus infection. In July, 2020, bulevirtide 2 mg received conditional marketing authorisation by the European Medical Agency for treatment of chronic hepatitis D virus infection. We investigated the antiviral activity of bulevirtide in patients chronically infected with HBV and hepatitis D virus. - Methods - MYR202 (ClinicalTrials.gov, NCT03546621; EudraCT, 2016-000395-13) was a multicentre, parallel-group, randomised, open-label, phase 2 trial. Adults (aged 18-65 years) with chronic hepatitis D virus infection, including patients with cirrhosis and patients who had contraindications to PegIFNα treatment or for whom treatment did not work, were eligible and were enrolled from four hospitals in Germany and 12 hospitals in Russia. Patients were randomly assigned (1:1:1:1) to receive 2 mg (n=28), 5 mg (n=32), or 10 mg (n=30) subcutaneous bulevirtide once per day with tenofovir disoproxil fumarate (TDF; 245 mg once per day orally) or TDF alone (245 mg once per day orally; n=30) for 24 weeks. Randomisation was done using a digital block scheme with stratification, consisting of 480 randomisation numbers separated into 30 blocks. The primary endpoint was undetectable hepatitis D virus RNA or 2 log10 IU/mL or higher decline in hepatitis D virus RNA at week 24, which was analysed in the modified intention-to-treat population, including patients who received study medication at least once after randomisation. Hepatitis D virus RNA concentrations were monitored until week 48. Safety was assessed for all patients who received at least one dose of bulevirtide or TDF. - Findings - Between Feb 16, 2016, and Dec 8, 2016, 171 patients with chronic hepatitis D virus infection were screened; 51 were ineligible based on the exclusion criteria and 120 patients (59 with cirrhosis) were enrolled. At week 24, 15 (54%, 95% CI 34-73) of 28 patients achieved undetectable hepatitis D virus RNA or a 2 log10 IU/mL or more decline in hepatitis D virus RNA (p<0·0001 vs TDF alone) with 2 mg bulevirtide, 16 (50%, 32-68) of 32 with 5 mg bulevirtide (p<0·0001), and 23 (77%, 58-90) of 30 with 10 mg bulevirtide (p<0·0001), versus one (4%, 0·1-18) of 28 with TDF alone. By week 48 (24 weeks after bulevirtide cessation), hepatitis D virus RNA concentrations had rebounded, with median changes from week 24 to week 48 of 1·923 log10 IU/mL (IQR 0·566-2·485) with 2 mg bulevirtide, 1·732 log10 (0·469-2·568) with 5 mg bulevirtide, and 2·030 log10 (1·262-2·903) with 10 mg bulevirtide. There were no deaths associated with treatment. Three (9%) patients in the bulevirtide 5 mg group, two (7%) patients in the bulevirtide 10 mg group, and one (4%) patient in the TDF group had serious adverse events. Common treatment-emergent adverse events included asymptomatic bile salt increases and increases in alanine aminotransferase and aspartate aminotransferase. - Interpretation - Bulevirtide induced a significant decline in hepatitis D virus RNA over 24 weeks. After cessation of bulevirtide, hepatitis D virus RNA concentrations rebounded. Longer treatment durations and combination therapies should be investigated. - Funding - Hepatera LLC, MYR GmbH, and the German Centre for Infection Research, TTU Hepatitis.
Gesehen am 16.05.2023